2002
DOI: 10.1046/j.1523-1755.2002.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP release in human kidney cortex and its mitogenic effects in visceral glomerular epithelial cells

Abstract: In human renal cortex, adrenergic stimulation releases ATP from neuronal and non-neuronal sources. ATP has mitogenic effects in vGEC and therefore the potential to contribute to progression in chronic renal disease. The pattern of purinoceptor agonist effects on DNA synthesis together with the mRNA expression suggests a major contribution of a P2Y1-like receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 41 publications
3
35
0
4
Order By: Relevance
“…In human renal cortex, sympathetic nerve stimulation releases ATP and NA, and NA acting on non-neuronal cells also releases ATP. The released ATP has mitogenic effects on glomerular epithelial cells, probably via P2Y 1 receptors, and ATP has the potential to contribute to remodelling of the kidney and progression to chronic renal failure, a condition that presents with sympathetic overactivity [391]. While P2X7 receptors are only weakly expressed in healthy glomerulus, following glomerular injury (for example, in diabetes and hypertension), it is significantly upregulated, mainly in podocytes, but also in endothelial and mesangial cells [393].…”
Section: Renal Injury and Failurementioning
confidence: 99%
“…In human renal cortex, sympathetic nerve stimulation releases ATP and NA, and NA acting on non-neuronal cells also releases ATP. The released ATP has mitogenic effects on glomerular epithelial cells, probably via P2Y 1 receptors, and ATP has the potential to contribute to remodelling of the kidney and progression to chronic renal failure, a condition that presents with sympathetic overactivity [391]. While P2X7 receptors are only weakly expressed in healthy glomerulus, following glomerular injury (for example, in diabetes and hypertension), it is significantly upregulated, mainly in podocytes, but also in endothelial and mesangial cells [393].…”
Section: Renal Injury and Failurementioning
confidence: 99%
“…Experimental studies showed that sympathetic overactivity is explained by increased afferent signals emanating from the kidney (43). In models of renal failure, one finds release not only of catecholamines but also of co-transmitters (44), and both may account for accelerated progression. The adverse effect of catecholamine excess on cardiac function is widely known, and a strong case can be made for the use of ␤ blockers in renal patients (45).…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…One of the distinct features of the sympathetic nervous system is the immediate regulation of peripheral vascular resistance through adaptation of the vascular tone. Besides this immediate action on blood pressure control through vasoconstriction, release of sympathetic neurotransmitters contribute to adaptive mechanisms through regulation of cell proliferation, transformation and apoptosis which are blood pressure independent [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%